Aerospace Clustering and its role in economic performance - Hladký, Ján (2015)
This dissertation thesis evaluates the role of aerospace clustering in the economic output. The focus on the clusters is based on the already existing theory, namely Michael Porter's book The Competitive Advantage of Nations in which he named clustering as one of the four essential factors that define the economic competitiveness of a country. On the other hand, the aerospace industry shows a huge potential with growing markets in Asia and in the run of the next decades, space exploration has to be reckoned with. In order to give a support to this theory and apply it to aerospace, a two stage analysis has been conducted. Firstly, Leontief's Input-Output analysis has been conducted, to show the importance of exports from this industry. Secondly, a model proposed by Hausmann et al. in 2007 has been adjusted to observe the productivity of aerospace commodities. The results of these analyses are positive and they give evidence to the importance of aerospace clustering. Moreover, they give merits to policy-makers' actions in this area.